(untitled) (Global Journal of Science Frontier Research, 2020)
Pollen morphological studies were investigated among three varieties of Impatiens balsamina to delimit, classify and trace probable evolutionary relationships and also provide a general reference system into which other kinds of information can be incorporated. Qualitative and quantitative morphological studies were carried out on each variety of Impatiens balsamina at their reproductive stage. Pollen grains from fresh anthers of three varieties of Impatiens balsamina from Botany Department, Obafemi Awolowo University, Osun State, Nigeria were collected and acetolysed. The structural morphology of the pollen grains carried out with light microscope is reported. Characters measured on the pollen grains were pollen diameter, pollen wall thickness, furrow diameter and pore diameter. This was done with the aid of ocular micrometer.